Contribuições das vozes sintéticas para o desenvolvimento da consciência fonológica em L2 - Gomes, Almir Anacleto de Araujo (2019)
This work seeks to understand and discuss how synthetic voices can contribute to phonological awareness development in L2 phonological acquisition. The discussion is firstly based on a theoretical investigation, supported by several empirical research on L2 phonological acquisition, aiming to understand the convergences and divergences among such investigations and thus build an insight of how phonological awareness can contribute to L2 phonological acquisition. Then, in order to corroborate such insight, an empirical data collection was carried out aiming to verify how a text-to-speech synthesizers tool can benefit Brazilian L2 learners in the acquisition of English past tense regular verbs [-ed] sound, by providing input rich in quantity, quality and variability. To verify the effectiveness of this tool, data were collected in individual single sessions, in which each participant performed a series of tasks developed to analyze phonological awareness evidence of these informants before and after using the text-to-speech synthesizer. Therefore, the discussion is based on studies of L2 phonological acquisition (ALCÂNTARA, 1998; ROCCA, 2003; ALVES, 2004, among others) and Computer-Assisted Language Learning - CALL studies, with research on synthetic voices in language learning (CARDOSO, SMITH AND GARCIA FUENTES, 2015; BIONE, 2017 AND ROSSINI, FRACARO, GOMES AND BRAWERMAN-ALBINI, 2018). It was noticed that the ability of reflecting on, analyzing, comparing and manipulating sounds of a language are the characteristics of what is called phonological awareness in L2 acquisition studies. So, it embraces those investigations on explicit instruction, formal instruction, formal knowledge, metalinguistic knowledge or other term regarding the specific characteristics of phonological awareness. It was detected that both at the level of perception and production, phonological awareness acts positively in the L2 phonological acquisition, contributing to a more effective communication, in view of the phonological awareness performance in the L2 sounds comprehensibility and intelligibility. Therefore, data, results and discussions of the analysed papers confirm the importance of phonological awareness in L2 phonological acquisition, as well as its relevance regarding the acquisition of L2-specific linguistic forms. Concerning the use of text-to-speech synthesizers in the development of L2 phonological awareness, the data revealed that its use complementarily to the classroom work can provide broad and individualized input to L2 learners in order to stimulate the development of their phonological awareness and thus, enhance the target language phonological acquisition.